ECONOMIC EFFICIENCY ASSESSMENT OF INVESTMENTS IN AGRICULTURAL PRODUCTION - Kuzman, Boris; Momčilović, Mirela; Ercegovac, Dajana; Milić, Dragana (Economics of Agriculture, 2023)
The purpose of this study is to assess the economic benefits of agricultural production and provide guidance to manufacturers and investors interested in agriculture. This paper applies dynamic efficiency evaluation methods i.e. net present value, profitability index, and internal rate of return, together with the sensitivity analysis that is useful in cases of market turbulences. The presented investment is purchasing 10 hectares of arable land and cultivating two alternative crops: corn and soybeans. Research results and projections imply that both scenarios are acceptable and economically profitable with the preference for the cultivation of corn giving better economic efficiency. This study can provoke further investment evaluations with dynamic capital budgeting methods in other crops or implementation of mechanization in agricultural production.